Penggunaan Aplikasi Animasi Interaktif (Animaker) Dalam Proses Pembelajaran - Anwar Three Millenium Waruwu; Herman Pakiding (Vox Dei: Jurnal Teologi dan Pastoral, 2023)
Using the Animaker application can expand the availability of teaching materials in the virtual world, allowing students to access them easily from home. Consequently, the utilization of Animaker in teaching can improve the effectiveness of learning by providing an enjoyable and engaging learning experience while also assisting in overcoming the limitations of technology usage in education in Indonesia. This research was conducted using a quantitative research method by distributing a questionnaire as a research instrument. This study aims to evaluate the impact of Animaker application usage in enhancing the learning experience of second-semester students at STT Ekumene Jakarta. Of the respondents who participated in the study, 55% agreed that using the Animaker application facilitated student understanding of learning material. Furthermore, 55% of the respondents also perceived that the utilization of the Animaker application assisted in enhancing student learning motivation.